Political Socialization in the Digital Knowledge Era (Journal of human and social sciences, 2023)
This study addresses political socialization in the context of the digital knowledge era and its rapid transformations. It highlights the role of modern technology, social networks, and intelligent systems in reshaping political values and culture, particularly in Arab societies. The study also explores the challenges and opportunities posed by the digital environment for political socialization, as well as the role of both traditional and modern institutions in fostering effective political participation among new generations.
Keywords: Political Socialization; Political Culture; Social Socialization; Digital Knowledge; Social Values and Norms